Efektivitas Penggunaan Media Sand Magic Untuk Meningkatkan Ketahanan Duduk Pada Anak Gangguan Pektrum Autisme - yulia, Rahmah Yulia; Rahmahtrisilvia, Rahmahtrisilvia (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
This research was motivated by the problems found in SLB YPPA Padang, there were 7-year-old autistic students who experienced problems in the duration of low sitting endurance. This study aims to prove the effect of sand magic media in increasing the sitting endurance of children with autism spectrum disorders in SLB YPPA Padang. The research method used is Single Subject Research (SSR) with an A - B - A design. Data collection under baseline conditions (A1) is continuous for 4 times, providing intervention using sand magic media (B) is carried out for 7 times, looking at conditions the second baseline (A2) for 4 times. the variables were analyzed using percentages. The results of the analysis of the ability to sit endurance during the learning process through sand magic media. At baseline conditions (A1) 0%, intervention conditions (B) 42%, and at baseline conditions (A2) 100%. The results of the study can be concluded that through the use of sand magic media can increase sitting endurance in GSA students.